Improved Stereoacuity Testing with the Judgement of Equal Distances - Larson, W.L. (Canadian Journal of Optometry, 2021)
Stereoacuity tests do not usually require the judgement of equal distances. A stereoacuity test which included zero disparity and required equal distance judgements was used to investigate the effect of overall aniseikonia on depth perception thresholds and the disparity of subjective equidistance ( DSE ). The results of this investigation are reported. The same data were used to determine the effect that a forced choice without the judgement of equal distances would have on test results. Three different ways of responding to a forced choice were simulated by redistributing equal distance responses between left and right nearer responses. These simulations often produced apparently better stereoacuities. From this, it is concluded that equal distance judgements improve the quality of stereoacuity test results.